Sulphur and Methionine Content of Some Freshwater Fishes of Madras - Sreenivasan, A.; Natarajan, M. V. (Fishery Technology, 1966)
The importance of sulphur aminoacids, especially of methionine, in our nutrition is too well known to be emphasized. But adequate data on the sulphur and methionine contents of the cheapest of our animal foods viz., fish, are not available. In this note, the total sulphur and methionine content of eighteen common fresh water fishes is presented.